Demineralization of Enamel in Primary Second Molars Related to Properties of the Enamel - N. Sabel; A. Robertson; S. Nietzsche; J. G. Norén (The Scientific World Journal)
Enamel structure is of importance in demineralization. Differences in porosity in enamel effect the rate of demineralization, seen between permanent and deciduous teeth. Individual differences have been shown in the mean mineral concentration values in enamel, the role of this in demineralization is not thoroughly investigated. The aim of this study was to study variations of depths of artificial lesions of demineralization and to analyze the depth in relation to variations in the chemical and mineral composition of the enamel. A demineralized lesion was created in second primary molars from 18 individuals. Depths of lesions were then related to individual chemical content of the enamel. Enamel responded to demineralization with different lesion depths and this was correlated to the chemical composition. The carbon content in sound enamel was shown to be higher where lesions developed deeper. The lesion was deeper when the degree of porosity of the enamel was higher.